2022
DOI: 10.1515/phon-2022-2023
|View full text |Cite
|
Sign up to set email alerts
|

Are Serbian and English listeners insensitive to lexical pitch accents in Serbian?

Abstract: The paper investigated possible “deafness” effects in the perception of lexical pitch accents by native and non-native listeners, that is, by Serbian and English listeners, respectively. The objective of the study was to explore which word-prosodic categories listeners used when they were required to contrast and recall sequences of lexical pitch accents. To that effect, Serbian and English listeners performed a Sequence Recall Task (SRT) in which they contrasted pairs of non-words with different Serbian lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A study on Czech English production reported that syllable stress was misplaced to the first syllable in about 50% of the stress alternation cases while all other alternatives (i.e., misplacing to the second, third or fourth syllable, erroneous addition or omission of stress) occurred with considerably lower probability ( Skarnitzl and Rumlová, 2019 ). Meanwhile, Polish has even been used to test what was termed as the “stress deafness” hypothesis ( Dupoux et al, 1997 ), now referred to as “stress insensitivity” [see Nikolić and Winters (2022) ]. This theory expects speakers of languages with fixed word stress (like Polish, Czech, and Macedonian) and speakers of languages with variable stress (like English, German, Bulgarian, and Serbian) to have varying sensitivity to word stress changes, depending on the amount of lexical exceptions to stress regularity in their native language ( Peperkamp et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study on Czech English production reported that syllable stress was misplaced to the first syllable in about 50% of the stress alternation cases while all other alternatives (i.e., misplacing to the second, third or fourth syllable, erroneous addition or omission of stress) occurred with considerably lower probability ( Skarnitzl and Rumlová, 2019 ). Meanwhile, Polish has even been used to test what was termed as the “stress deafness” hypothesis ( Dupoux et al, 1997 ), now referred to as “stress insensitivity” [see Nikolić and Winters (2022) ]. This theory expects speakers of languages with fixed word stress (like Polish, Czech, and Macedonian) and speakers of languages with variable stress (like English, German, Bulgarian, and Serbian) to have varying sensitivity to word stress changes, depending on the amount of lexical exceptions to stress regularity in their native language ( Peperkamp et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%